Technical Efficiency of the Indonesian Textile and Textile Product Industry - Amaliyah, Imroatul; Sari, Dyah Wulan; Yasin, Mohammad Zeqi (Universitas Airlangga, 2022)
This study investigates the determinants of the Indonesian textile and textile product (TPT) industry's technical efficiency. Employing the rich, balanced panel data of 3,365 firms over 2007-2013 with a non-parametric approach to the Data Envelopment Analysis (DEA) Bootstrapping and Tobit regression, this study discovers that the production operations are inefficient, especially the companies upstream. The improvement of technical efficiency is driven by firm size, market concentration, foreign ownership, and exports. An intriguing finding is that the capital-labour ratio negatively impacts efficiency, implying higher capital for production will make the production even more inefficient. The machines in most TPT firms are old, so larger capital may not help. This study recommends the government design policies that support the machinery restructuration so that capital can support production efficiency.